Performance of An Aerated Wastewater Stabilization Pond for the Treatment of Cultivation Wastewater of Pacific White Shrimp (Litopenaeus vannamei) Grow-out Ponds - Jannah, Rizkiyah Fatikhatul; Ratnawati, Ratnawati; Sunaryo, Sunaryo; Widiasa, I Nyoman (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
Pacific white shrimp (Litopenaeus vannamei) is a major cultivated crustacean species whose aquaculture production has doubled in the last decade. The implementation of shrimp pond systems using closed or intensive methods is widely carried out. However, wastewater produced by intensive shrimp farming may cause environmental effects. This study is aimed to evaluate the feasibility of the aerated wastewater stabilization pond to treat the cultivation wastewater. The physicochemical parameters monitored were temperature, pH, salinity, ammonia, nitrite, nitrate and phosphate. In the case of this study, almost all physicochemical parameters of the water coming out of the aerated wastewater stabilization pond are suitable for use as input water for integrated multitrophic aquaculture (IMTA). Temperature, pH, salinity, nitrite, nitrate, and phosphate were 27.1°C to 32.2°C, 7.86 to 8.79, 30 ppt to 34 ppt, 0.003 mg/L to 0.068 mg/L, and 0.19 mg/L to 1.31 mg/L, respectively. Only ammonia concentration significantly fluctuated in the range of 0.44 mg/L to 12 mg/L.